A Comparison of Heterogeneous/Homogeneous Crystallization for Phosphate Recovery from Biosolids. (1st September 2018) - Lin, Nan‐Hung; Hsieh, Yung‐Hsu; Chuang, Shun‐Hsing; Wu, Chun‐Hao; Huang, Yao‐Hui
Abstract : In this study, a fluidized bed reactor was used to compare heterogeneous and homogeneous crystallization for recovering magnesium ammonia phosphate (MAP) from the dewatering filtrate at a municipal water resource recovery facility. Investigating the factors affecting crystallization revealed that pH exerted a greater effect than the Mg/P molar ratio. The results of a heterogeneous crystallization experiment showed that removal efficiency of phosphate (RP%) and crystal efficiency of phosphate (CP%) were 68% and 66%, respectively, at a PO4 ‐P concentration of 200 mg/L, pH of 8.0, and Mg/P molar ratio of 1.0 for 3 h. The reaction rate of heterogeneous crystallization was markedly higher than that of homogeneous crystallization. Those pellets produced through the heterogeneous crystallization exhibited a dense surface (particle size 0.5‐1.0 mm; water content 8.7%). Through scanning electron microscopy (SEM), energy dispersive x‐ray spectroscopy (EDS), and X‐ray diffraction (XRD) examination, the crystallized patterns of the needle‐shaped pellets were identified as MgNH4 PO4 ·6H2 O.